Consequence assessment using threat zone analysis on sulphuric acid production plant / Mohd Aizad Ahmad, Wan Nur Atikah Nabila Wan Badli Shah and Zulkifli Abdul Rashid - Ahmad, Mohd Aizad; Wan Badli Shah, Wan Nur Atikah Nabila; Abdul Rashid, Zulkifli (Universiti Teknologi MARA, 2021)
The consequence assessment is one of the crucial methods in the process safety engineering fields to determine and quantify the threat zone derived on the respective chemical plant and this method will guide the designer regarding the most suitable preventive measure to avoid the disaster of a chemical plant. This work highlights the consequence assessment on sulphuric acid production plant using threat zone analysis, one of the steps in Quantitative Risk Assessment. The plant has decided to produce 80,000 MT per year of sulphuric acid in Malaysia with the selected site location of Kerteh, Terengganu. The process layout and location of the equipment installed for the processing steps of sulphuric acid production have been simulated by the Aspen HYSYS simulation software. All possible hazardous chemical for every equipment has been identified and the consequence assessment method focusing on threat zone distance was developed through the six steps of methodology to estimate the worst-case scenario. Distance of threat zone was simulated using ALOHA, MARPLOT and Google Earth software. Results show that the absorber tower produces the worst-case scenario among all equipment in the plant, which red threat zone of toxicity reaches more than 10 km to the surrounding area.